(untitled) (Altre Modernità, 2022)
Maria Teresa Chialant, Racconti d’amore al tempo della Regina Vittoria (Napoli, Edizioni Scientifiche Italiane, 2020, 208 pp. ISBN 978-88-495-4195-3) di Elena Ogliari